Working People Built BC - BC Labour Heritage Centre (Working People Built BC, 2004)
The BC Labour Heritage Centre Society was founded in 2004 with JJ (Jack) Munro as Chair. The Society preserves, documents and presents the rich history of working people in British Columbia. The Society engages in partnerships and projects that help define and express the role that work and workers have played in the evolution of social policy and its impact on the present and future shaping of the province. --Website "About" page.

Gender & Work Database - York University. Department of Politics; Vosko, Leah F. (2004)
The Gender & Work Database (GWD) is an online research tool designed for both researchers and students with varying levels of expertise. The database is informed by a feminist political economy approach and provides resources that facilitate research on gender and work. The GWD can be used as an interactive classroom tool, to obtain basic information on a topic, or as a research tool to examine complex social relations. ...[Following the introduction to the database,] there are six integrated and interactive modules that represent entry points into the study of gender and work, namely precarious employment, health care, unions, migration, unpaid work, and technology. --Website description